Pelvic antropometric measurement in 3D CT for placement of two unilateral iliosacral S1 - 7.3 mm screws - Höppchen, Arnold; Helm, Elisabeth; Obertacke, Udo (International orthopaedics, 2021)
Stability of the dorsal pelvic ring is important for patient mobilisation and can be restored using several surgical procedures after fracture. Placement of percutaneous iliosacral screws is a reliable and minimal-invasive technique to achieve stabilisation of the dorsal pelvic ring by placement of two screws in the first sacral vertebra. Aim of this study was to evaluate 3D CT scans regarding the anatomical possibility to place two 7.3 mm iliosacral screws for fixation of the dorsal pelvic ring.